Analisis Perbandingan Dampak Serangan Black Hole Pada Kinerja Routing Protocol LAR (Location-Aided Routing) dan DYMO (Dynamic Manet On-Demand) di Mobile Ad-Hoc Network (MANET) - I Dewa Gede Ardana Pucanganom; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mobile Ad-Hoc Network is a network consisting of nodes that can move in all directions (mobile). These nodes can communicate with temporary communication channels). On mobile ad-Hoc networks, routing protocol is useful in determining the best data packet delivery path. Issues that exist in the MANET network are limited bandwidth, energy, transmission range, and security. In the security aspect, data packet is still vulnerable to forms of attack, one of them is black hole that can dropping data packets. To knowing the routing protocol's performance against black hole attacks, then the performance analysis of reactive routing protocols (Dynamic MANET On-Demand and Location-Aided Routing) needed. When black hole run, the average value of packet delivery ratio routing protocol LAR and DYMO is 51.38% and 51.92%. The average end to end delay value of LAR and DYMO routing protocol is 70.58 ms and 24.01 ms. The average value of normalized routing load of routing protocol LAR and DYMO is 2.68 and 1.38. Based on the comparison of these average values, the DYMO routing protocol gets better performance than the LAR routing protocol in the normalized routing load, average end to end delay and packet delivery ratio parameters when black hole is run.